Excursions in harmonic analysis : the February fourier talks at the Norbert Wiener center - Andrews, Travis D; Balan, Radu; Benedetto, John J.; Czaja, Wojciech; Okoudjou, Kasso A. (New York : Birkhauser, 2013)
This two-volume set consists of contributions from speakers at the February Fourier Talks (FFT) from 2006-2011. The FFT are organized by the Norbert Wiener Center in the Department of Mathematics at the University of Maryland, College Park. These volumes span a large spectrum of harmonic analysis and its applications. Each part provides state-of-the-art results, with contributions from an impressive array of mathematicians, engineers, and scientists in academia, industry, and government. Excurisions in Harmonic Analysis: The February Fourier Talks at the Norbert Wiener Center is an excellent reference for graduate students, researchers, and professionals in pure and applied mathematics, engineering, and physics --
V. 1. I. Sampling theory ; II. Remote sensing ; III. Mathematics of data processing ; IV. Applications of data processing -- V. 2. V. Measure theory ; VI. Filtering ; VII. Operator theory ; VIII. Biomathematics.
Selected conference papers.
Includes bibliographical references and indexes.
Keywords: Harmonic analysis